Upper and Lower Rarely m-I-Continuous Multifunctions (European Journal of Pure and Applied Mathematics, 2024)
In 1979, Popa [24] first introduced rarely continuous functions. In this paper, we introduce upper and lower rarely m-continuous multifunctions. Moreover, we extend this concept to a multifunction F : (X, τ, I) → (Y, σ), where (X, τ, I) is an ideal topological space.